Nurse's Legal Handbook. - Springhouse (Wolters Kluwer Health, 2004)
The newly revised Fifth Edition of this handbook is an up-to-the-minute, authoritative guide to the legal and ethical issues faced daily by nurses. Replete with real-life examples and information from hundreds of court cases, the book covers the full range of contemporary concerns, including computer documentation, cloning, stem cell research, pain management, euthanasia, prescribing, privacy, and confidentiality as well as the nursing shortage. New topics include workplace violence and harassment, needlesticks, telephone triage, and quality assurance. A new Legal Tip logo highlights proactive.